Impact of Wetland Urbanization in Kuala Lumpur, Malaysia - Ali, Maisarah; Jusoff, Kamaruzaman (2007)
Wetlands provide an important ecological function that contributes to watershed functions, most notably in pollutant removal, flood attenuation, groundwater recharge and discharge, shoreline protection, and wildlife habitat. However, despite of the many watershed services wetlands provide, the pressure from the development of a city is great. This research is carried out to identify the threats that will affect wetlands and the surrounding area undergoing development by using several methodologies, namely observations, photograph analysis and interviews. The area chosen for the study is a wetland in the township of Kota Damansara, a suburb of Kuala Lumpur, the commercial city of Malaysia. The undergoing development of the area, reclaiming17.66 acres of the total 45.89 acres water retention lake to build 6 blocks of apartment and commercial units will create adverse impacts to the area down stream. Moreover, it is believed that the collapse of a bund in the wetland in 2006 had compounded towards the massive flood situation in other cities located down stream. This event more or less provides an attestation to the function and the role of this wetland and the impacts that may occur if it were to undergo any changes. There is a need to compromise between conservation and development as conservation of wetlands is of great significance in preventing flooding.